Development, Pathogenesis, and Regeneration of the Intervertebral Disc: Current and Future Insights Spanning Traditional to Omics Methods - Hickman, Tara T.; Rathan-Kumar, Sudiksha; Peck, Sun H. (Frontiers in Cell and Developmental Biology, 2022)
The intervertebral disc (IVD) is the fibrocartilaginous joint located between each vertebral body that confers flexibility and weight bearing capabilities to the spine. The IVD plays an important role in absorbing shock and stress applied to the spine, which helps to protect not only the vertebral bones, but also the brain and the rest of the central nervous system. Degeneration of the IVD is correlated with back pain, which can be debilitating and severely affects quality of life. Indeed, back pain results in substantial socioeconomic losses and healthcare costs globally each year, with about 85% of the world population experiencing back pain at some point in their lifetimes. Currently, therapeutic strategies for treating IVD degeneration are limited, and as such, there is great interest in advancing treatments for back pain. Ideally, treatments for back pain would restore native structure and thereby function to the degenerated IVD. However, the complex developmental origin and tissue composition of the IVD along with the avascular nature of the mature disc makes regeneration of the IVD a uniquely challenging task. Investigators across the field of IVD research have been working to elucidate the mechanisms behind the formation of this multifaceted structure, which may identify new therapeutic targets and inform development of novel regenerative strategies. This review summarizes current knowledge base on IVD development, degeneration, and regenerative strategies taken from traditional genetic approaches and omics studies and discusses the future landscape of investigations in IVD research and advancement of clinical therapies.